Intertriginous drug eruptions - Mahajan Vikram; Sharma Ramesh (Wolters Kluwer Medknow Publications, 2005)
Drug eruptions confined to intertriginous areas are rare and unusual cutaneus manifestations of amoxicillin sensitivity. We describe here three such cases of intertriginous drug eruptions. Two of these patients had developed fexural exanthematous rash and mild systemic symptoms following amoxicillin administration while in the third it was due to, hitherto unreported, celecoxib. Their possible patho-mechanism in the light of current knowledge is also discussed.